Business Cycles and the Synchronisation Process: A Bounds Testing Approach - Chan, Tze Haw; Lau, Evan Poh Hock (INTI Publishing House Sdn Bhd, 2005)
To justify the business cycle synchronization (BCS) process among ASEAN-5 (Indonesia, Malaysia, Philippines, Singapore and Thailand), Japan and the United States, the Autoregressive Distributed Log bounds test and the UECM (Unrestricted Error Correction Model) representation advanced in Pesaran et al. (2001) is deployed. Evidently, ASEAN-5 has achieved some important degree of business cycle co fluctuations, attributed to improved intra trading and cross-boarder investments. Nonetheless, the idiosyncratic and common shocks in ASEAN economies are more identical to the Japanese experience rather than the US experience. Comparable patterns of economic development and liberalisation process have created countries (ASEAN-Japan) with similar economic structures, implying that further economic cooperation and currency arrangements in the region are bright. In addition, our findings demonstrate that the bilateral exchange rate stability may not contribute to the business cycle convergence, as in the ASEAN-US case while bilateral exchange rate dispersion has not jeopardised the ASEAN-Japan BCS process. Also, price divergences among the ASEAN-US-Japan indicate that there is scope for further price convergence if the Japanese Yen or the US dollar is to be adopted as the common currency. Nonetheless, a coordinated regional policy should focus on narrowing the yen/dollar fluctuation, ahead of forming a common currency area or monetary union.